Perencanaan Arsitektur Sistem Informasi Pengarsipan Surat dengan Menggunakan Metode EAP - Tryana, Anjas; Larasati, Larasati (Jurnal Accounting Information System (AIMS), 2025)
The Al Ma’soem Foundation in Bandung has a Public Relations (PR) department responsible for letter archiving. Currently, the archiving process is still done manually using Microsoft Office and physical archive boxes, which is considered less effective and efficient. Common issues include difficulty in locating letters, data loss, and document damage. To address these problems, this study aims to design an information system architecture for letter archiving using the Enterprise Architecture Planning (EAP) method with cloud computing integration. The EAP method consists of several stages, including planning initiation, business modeling, data architecture, application architecture, technology architecture, and implementation planning. The results of this study produce a framework (blueprint) that includes 4 main business processes, 17 data entities, 6 applications, and proposed cloud-based technology solutions. By implementing cloud computing, the letter archiving system is expected to become more efficient, secure, and easily accessible, thereby supporting the organization's operational efficiency. This study also provides implications for other organizations looking to improve their archiving systems through cloud computing technology.